Psychological factors of secondary school graduates’ hardiness - Serdiuk, Liudmyla; Danyliuk, Ivan; Chykhantsova, Olena (Social Welfare: Interdisciplinary Approach, 2019)
The article examines the personal qualities of secondary school graduates that determine their hardiness at their professional self-determination. The modern approaches defining hardiness essence and factors, and peculiarities of its development are analyzed. The factors contributing to the enhancement of an individual’s hardiness in the situation of professional self-determination are considered. Hardiness is understood as a holistic phenomenon of a personality that mediates stress impact on psychological well-being and health. Self-understanding and self-acceptance of secondary school graduates, their life goals, and life meanings, confidence in themselves and their capabilities are important. It is the psychological basis of personal resilience and life senses.